Indirect focused written corrective feedback on elementary ESL learners’ writing / Sim Chiang Huey - Sim , Chiang Huey (2019)
This study investigates the efficacy of indirect focused written corrective feedback (IFWCF) on simple past tense errors of two distinct groups of elementary ESL pupils (high and low proficiency level) through a 6-week intervention. Comparison between pretest and posttest was made within groups using paired sample t-test and between groups with Mann-Whitney U test. Based on the findings, the intended measure was effective for the high proficiency group but not the low proficiency group, yet no significant difference was observed between those two groups. Semi-structured interviews were also conducted with ten selected participants with the most significant difference in their pretest and posttest scores to probe their perceptions towards the usefulness of the measure towards their use of simple past tense in their descriptive writing. From the thematic analysis conducted, four major themes were identified. It was revealed that the intended measure was effective in cultivating error identification ability, promoting critical thinking skills, regulating problem solving skills and improving implicit knowledge. Due to the limited sample size, generalization cannot be made upon the population outside the study.